Sensitivity and specificity of assessment scales of dentin hypersensitivity - an accuracy study - Mariana Oliveira Cotta ROCHA; Aléxia Aguiar Carvalho Fonseca CRUZ; Daniella Oliveira SANTOS; Dhelfeson Willya DOUGLAS-; Olga Dumont FLECHA; Patricia Furtado GONÇALVES (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of the present study was to compare the sensitivity and specificity of pain scales used to assess dentin hypersensitivity (DH). The preferred scale, and toothbrushing habits of participants were also investigated. This cross-sectional study was conducted with students and employees of a Brazilian Federal University who presented DH. The participants answered a questionnaire about their toothbrushing and drinking habits. Hypersensitive and non-sensitive teeth were submitted to tactile and ice stick stimuli. Then, the subjects marked their pain level in the visual analogue (VAS), numeric scale (NS), faces pain scale (FPS) and verbal evaluation scale (VES). DH was also assessed by Schiff scale (SS). The data were analyzed by Wilcoxon and Chi-Square tests, as well as by ROC curve. The mean age of the sample (56 women, 16 men) was 27.8 years. The most prevalent acidic beverage was coffee (36.0%) and the most preferred scale was the NS (47.2%). The pain level was statistically higher in teeth with DH compared to teeth without DH (p < 0.05). The accuracy ranged from 0.729 (SS) to 0.750 (NS). The highest sensitivity value was 81.9% for NS. The SS presented the highest specificity (91%). The visual analog, numerical, verbal evaluation, faces pain, and Schiff scales were accurate for DH diagnosis. The Schiff scale was the preferred scale for DH assessment.